(3GdJOhjf aj PcQ CNHGQ bRhjfs - (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf s
(3QJH GdJQGLe ajgG Ydi JQJjH GdMQha GdgLGFjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B3s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B393 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdHdOjI HGdGScfOQjI (B(810 (3H(B) s
Keywords: (3GdJGQjNs